Novel Therapeutic Targets in Depression and Anxiety: Antioxidants as a Candidate Treatment - Xu, Ying; Wang, Chuang; J. Klabnik, Jonathan; M. O' Donnell, James (Current Neuropharmacology, 2014)
There is growing evidence that the imbalance between oxidative stress and the antioxidant defense system may be associated with the development neuropsychiatric disorders, such as depression and anxiety. Major depression and anxiety are presently correlated with a lowered total antioxidant state and by an activated oxidative stress (OS) pathway. The classical antidepressants may produce therapeutic effects other than regulation of monoamines by increasing the antioxidant levels and normalizing the damage caused by OS processes. This chapter provides an overview of recent work on oxidative stress markers in the animal models of depression and anxiety, as well as patients with the aforementioned mood disorders. It is well documented that antioxidants can remove the reactive oxygen species (ROS) and reactive nitrogen species (RNS) through scavenging radicals and suppressing the OS pathway, which further protect against neuronal damage caused oxidative or nitrosative stress sources in the brain, hopefully resulting in remission of depression or anxiety symptoms. The functional understanding of the relationship between oxidative stress and depression and anxiety may pave the way for discovery of novel targets for treatment of neuropsychiatric disorders.
Keywords: Antidepressants